2017
DOI: 10.1021/acs.jpcc.7b03020
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the Properties of Transparent Al-Doped ZnO Thin Film Electrodes Exposed to Ambient Air

Abstract: The properties of Al-doped ZnO (AZO) films are known to degrade with exposure to humidity. Different AZO films deposited using reactive direct current magnetron sputtering (DCMS) and high power impulse magnetron sputtering (HiPIMS) have been aged in ambient laboratory conditions and annealed at temperatures between 160 and 180 °C in a N2 atmosphere. Their electrical and optical properties, which have been investigated both ex situ and in situ during the annealing, are improved. The results of the in situ measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…A decrease in Hall mobility was comparably exhibited by all samples (Figure and ), which indicated the diffusion of water molecule‐derived species or oxygen molecules to the AZO thin films, thus increasing electron scattering at grain boundaries as reported by Mickan et al Figure shows the evolution of carrier concentration and Hall mobility as a function of annealing temperature of each sample before and after the damp heat test compared to the recovered results. After the damp heat test, carrier concentration and Hall mobility decreased for all samples where the highest carrier concentration and Hall mobility were maintained in AZO samples annealed at 550 °C.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…A decrease in Hall mobility was comparably exhibited by all samples (Figure and ), which indicated the diffusion of water molecule‐derived species or oxygen molecules to the AZO thin films, thus increasing electron scattering at grain boundaries as reported by Mickan et al Figure shows the evolution of carrier concentration and Hall mobility as a function of annealing temperature of each sample before and after the damp heat test compared to the recovered results. After the damp heat test, carrier concentration and Hall mobility decreased for all samples where the highest carrier concentration and Hall mobility were maintained in AZO samples annealed at 550 °C.…”
Section: Resultssupporting
confidence: 65%
“…A grain boundary reconstruction of AZO films was suggested by Hüpkes et al where grains grew together and closed grain boundaries partially on the cost of other areas due to annealing. Mickan et al reported that annealing in a nitrogen atmosphere at 180°C could restore the property of sputtered AZO thin films aged for 6 months in the ambient air, where out‐diffusion of water molecule was suggested as the reason for the restored property of the films. This evidence might suggest no physical damage during the degradation test of AZO films.…”
Section: Introductionmentioning
confidence: 99%
“…The band-to-band absorption in the In-doped ZnO has proved existence of energy transfer between ZnO and indium [22] by peaks marked as 378 nm (3.28 eV) [23]. The case of peaks at 400 (3.1 eV) [24] and 409 nm (3.03 eV) [25] maybe originates from zinc vacancies as well as transitions between conduction band and Zn vacancies as acceptor levels in this structure. Based on results, some weak intensity peaks are also observed at 444, 468, 481 and 491 nm in the measured spectra.…”
Section: Resultsmentioning
confidence: 75%
“…It becomes weaker with increasing annealing temperature at 300-700 • C due to the removal of these impurities by annealing. It has been reported in the case of AZO films deposited by reactive HiPIMS stored in ambient air contain hydroxyl groups in the bulk of the film, and these groups are released after subsequent annealing in reducing atmosphere [36]. The film resistivity significantly decreases after this release.…”
Section: Resultsmentioning
confidence: 97%